Modified decision-making rule supported by scheduled telephone follow-up reduces head computed tomography utilization in children with mild traumatic brain injury: A cohort study. Issue 18 (May 2020) - Zou, Liqun; Li, Hong; Jiang, Zhen; He, Bin; Xie, Yong; Zhang, Wei; Jiang, Jingyuan; Nie, Hu
Abstract : Abstract: Unnecessary computed tomography utilization is common in children with a mild traumatic head injury. It is valuable to find a reasonable strategy for the patient's management. The aim of this study was to investigate the effect of scheduled telephone follow-up on computed tomography utilization in children with a mild head injury. A 2-year cohort study was performed. Children diagnosed with mild traumatic brain injury (TBI) were evaluated with a scoring system upon their arrival and during 1 month of scheduled telephone follow-ups by nurses. The rates of head computed tomography utilization, delayed imaging, and delayed diagnosis were analyzed. The rate of computed tomography utilization was 64.3% and 46.1% ( P  = .00) in the retrospective and prospective study periods, respectively. During the prospective study period, there were no differences in the rates of delayed imaging (2.3% vs. 2.2%, P  = .814) or the rates of delayed diagnosis of significant radiological findings (0.1% vs 0.2%, P  = .672) in cases with versus without immediate computed tomography. Adoption of a modified decision-making rule supported by scheduled telephone follow-up can reduce head computed tomography utilization without increasing the rate of missed or delayed diagnosis of clinically significant TBI in children with mild TBI.